2023
DOI: 10.3390/ijerph20031661
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality in Aging: The Association with Mental Health

Abstract: Sleep disturbances are common in the elderly. A primary sleep disorder can result from the physiological decline of aging; however, secondary sleep problems result from various causes involving physical and mental health. Since little is known about the relationships between sleep quality and mental health in aging, the present study aims to understand how different aspects generally associated with sleep (e.g., psychological and physiological factors, and sleep medication) may predict poor sleep quality in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…However, another study did not find evidence for associations between self-reported sleep and neural health, as evidenced by a mostly stable relationship across a lifespan, and the absence of any strong relation (after controlling for age) between sleep quality and neural health (i.e., fractional anisotropy) above and beyond old age [24]. Sleep quality may also be altered with age, due to changes in the mental health conditions, as well as the use of sleep medication [54]. Taken together, age-related changes in sleep patterns appear to be complex and multifaceted, and warrant further experimental neurophysiological research.…”
Section: Discussionmentioning
confidence: 75%
“…However, another study did not find evidence for associations between self-reported sleep and neural health, as evidenced by a mostly stable relationship across a lifespan, and the absence of any strong relation (after controlling for age) between sleep quality and neural health (i.e., fractional anisotropy) above and beyond old age [24]. Sleep quality may also be altered with age, due to changes in the mental health conditions, as well as the use of sleep medication [54]. Taken together, age-related changes in sleep patterns appear to be complex and multifaceted, and warrant further experimental neurophysiological research.…”
Section: Discussionmentioning
confidence: 75%
“…Several types of physical activity suitable for older people include walking, yoga, and light exercise. 3) Adopt healthy sleep habits: Poor sleep habits can increase the risk of stress in the elderly (17). Make sure to get enough sleep at the same time every day to help relieve stress.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review has highlighted the presence of AM impairment in patients with MCI. These impairments could worsen MCI patients' performances in many domains, not only related to cognitive functioning, and can be affected by many impaired aspects in elderly people, such as sleep quality and mental health [61,62]. Therefore, it is extremely important to investigate these aspects further, also considering some relevant aspects, such as cognitive reserve [63], in order to develop psychological interventions to improve memory of the past.…”
Section: Discussionmentioning
confidence: 99%